Changes in physical activity behaviour and physical function after bariatric surgery: a systematic review and meta‐analysis. (18th January 2016) - Herring, L. Y.; Stevinson, C.; Davies, M. J.; Biddle, S. JH.; Sutton, C.; Bowrey, D.; Carter, P.
Summary: Although physical activity performed after bariatric surgery is associated with enhanced weight loss outcomes, there is limited information on patients' physical activity behaviour in this context. This systematic review and meta‐analysis assessed pre‐operative to post‐operative changes in physical activity and physical function outcomes among obese adults undergoing bariatric surgery. A total of 50 studies met inclusion criteria with 26 papers reporting data for meta‐analysis. Increases in both objectively recorded and self‐reported physical activity at 12 months were demonstrated. Studies indicated that there was a shift towards a greater amount of active time, but of a lower intensity within the first 6 months of bariatric surgery, suggested by a reduction in moderate to vigorous physical activity but an increase in step count. A standardized mean difference (SMD) of 1.53 (95% CI: 1.02–2.04) based on nine studies indicated improved walking performance at 12 months. Similarly, analysis of five studies demonstrated increased musculoskeletal function at 3–6 months (SMD: 1.51; 95% CI: 0.60–2.42). No relationship was identified between changes in weight and walking performance post‐surgery. More studies assessing physical activity, physical function and weight loss would help understand the role of physical activity in optimizing post‐operative weight and functional outcomes.